The Small Secreted Protein FoSsp1 Elicits Plant Defenses and Negatively Regulates Pathogenesis in Fusarium oxysporum f. sp. cubense (Foc4) - Wang, Yuhua; Zhang, Xinchun; Wang, Tian; Zhou, Siyu; Liang, Xiaofei; Xie, Changping; Kang, Zhensheng; Chen, Daipeng; Zheng, Li (Frontiers in Plant Science, 2022)
Fusarium wilt of banana (Musa spp.), a typical vascular wilt disease caused by the soil-borne fungus Fusarium oxysporum f. sp. cubense race 4 (Foc4), seriously threatens banana production worldwide. Pathogens, including vascular wilt fungi, secrete small cysteine-rich proteins during colonization. Some of these proteins are required for pathogenicity. In this study, 106 small secretory proteins that contain a classic N-terminal signal peptide, were identified by bioinformatic methods in Foc4. Among them, 11 proteins were selected for transient expression in tobacco. Interestingly, transient expression of FoSsp1, an uncharacterized protein (of 145 aa), induced necrotic cell death reactive oxygen burst and callous deposition. Furthermore, the expression of FoSSP1 was up-regulated during the stage of colonization. A split-marker approach was used to knock out FoSSP1 in the Foc4 wild type strain. Compared with the wild type, the deletion mutant Fossp1 was normal in vegetative growth but increased in conidiation and virulence. RT-qPCR analysis showed that the expression of conidiation regulator genes and Pathogenesis-Related (PR) genes were down-regulated in the Fossp1 deletion mutant. In summary, these results suggested that FoSSP1 is a putative elicitor which negatively regulates conidiation and pathogenicity in Foc4.